Restrictions on Digital Transformation on Micro and Small Enterprises in Kolaka Regency - Sapriyadi, Sapriyadi; Ilham, Surianto; Zizih, Andi Rezah Tenri (Equity: Jurnal Ekonomi, 2026)
The results of the National Digital Transformation Index (TDN) measurement in Southeast Sulawesi Province in 2022 are 44, indicating that digital transformation is still classified as C (adequate). Limited technology adoption and low innovation in business among micro and small business actors are one of the causes of low performance in the business pillar, which affects the acquisition of the TDN Index score. This study aims to investigate the factors that inhibit the implementation of digital transformation among micro and small business actors in Kolaka Regency. The sample in this study is 106 micro and small business actors with various types of businesses, including culinary, fashion, handicrafts, and agribusiness. Binary logistic regression analysis was used to estimate the inhibiting factors influencing the implementation of digital transformation in micro and small businesses. The study's findings reveal that digital knowledge, digitalization training, and digital transaction security are the primary factors hindering digital transformation among micro and small business actors in Kolaka Regency. Micro and small business actors who are unable to access information and participate in the digital community, have not received digital marketing and financialization training, and have not utilized the official digital transaction system are more likely to remain digitally untransformed. Meanwhile, the availability of digital devices and digital ecosystems does not have a significant influence on digital transformation. These findings recommend strategies to enhance digital transformation for micro and small business actors by focusing on increasing digital literacy and knowledge, continuous digitalization training, and building trust in the security of digital transactions.